Clinical and Humoral Determinants of Congestion in Heart Failure: Potential Role of Adiponectin - Monzo, Luca; Kotrc, Martin; Benes, Jan; Sedlacek, Kamil; Jurcova, Ivana; Franekova, Janka; Jarolim, Petr; Kautzner, Josef; Melenovsky, Vojtech (Kidney & blood pressure research, 2019)
BACKGROUND: Some patients with heart failure (HF) are more prone to systemic congestion than others. The goal of this study was to identify clinical and humoral factors linked to congestion and its prognostic impact in HF patients. METHODS: A total of 371 advanced HF patients underwent physical examination, echocardiography, right heart catheterization, blood samplings, and Minnesota Living with HF Questionnaire. Subjects were followed-up for adverse events (death, urgent transplantation, or assist device implantation without heart transplantation). RESULTS: Thirty-one percent of patients were classified as prone to congestion. During a median follow-up of 1,093 days, 159 (43%) patients had an adverse event. In the Cox analysis, the congestion-prone (CP) status was associated with a 43% higher event risk. The CP status was strongly (p ˂ 0.001) associated with body weight loss, right ventricular dysfunction (RVD), dilated inferior vena cava (IVC), diuretics, and beta-blockers prescription and the majority of tested hormones in the univariate analysis. In the multivariate analysis, the only independent variables associated with the CP status were adiponectin, albumin, IVC diameter, and RVD. Adiponectin by itself was predictive of adverse events. In a multivariate model, CP status was no longer predictive of adverse events, in contrast to adiponectin. CONCLUSIONS: CP patients experienced more severe symptoms and had shorter survival. Potential role of adiponectin, a new independent predictor of CP status, should be further examined.
Keywords: Prognosis; adiponektin; Adiponectin; Middle Aged; mužské pohlaví; Heart failure; ženské pohlaví; prognóza; Humans; Right ventricular dysfunction; lidé středního věku; srdeční selhání; Congestion; rizikové faktory; Female; Risk Factors; Heart Failure; lidé; Male